Application of Fuzzy Logic to Determine Gonad Maturity Level Based on Patin Fish Parent Morphology - Zevanya Gultom; Muhammad Danang Mukti Darmawan; Ester Angeline; Nanda Octavia; Ida Bagus Wahyu Rizky Himayasa Putra; Bima Widya S; Shepia Wardina; Dini Anisa Amaliasari; Amanda Bhanuwatie; Naura Nazhara N; Naufalariq Syawal Athallah; M. Aldo Ramdhan Pratama; Maulana Ishaq; Gavrilan Hafiz Rangkuti; Camelia Trirahmawati; Afifah Nur Lina Putri; Ilham Galeh Ramadhan; Debora Florence Nainggolan; Fiqri Nurfadillah (Batrisya Education, 2025)
The fish gonad maturity detector uses fuzzy logic to provide information about the level of gonad maturity accurately. The utilization of fuzzy logic in determining the level of maturity of catfish gonads offers significant advantages over traditional methods. The data collection method used is qualitative through direct observation of the characteristics of catfish broodstock in the rearing pond as well as literature study of previous research. Observations were made to understand the physical characteristics, while the literature study was to support the creation of a fuzzy logic system. The system has an initial stage in determining fuzzy sets for input and output variables, as well as the formation of fuzzy rules using IF-THEN. including better accuracy and the ability to accommodate individual variations and environmental conditions. Traditional methods of determining the maturity level of fish gonads, such as visual observation and GSI calculation, have their own weaknesses. Therefore, the application of fuzzy logic can help reduce the risks and side effects experienced by fish, and increase the effectiveness and efficiency in determining the level of maturity of catfish gonads.